Efficacy and Safety of Anti-Osteoporotic Agents across CKD Stages: A Meta-Analysis of Randomized Clinical Trials - Tahereh Sabaghian; Parisa Delkash; Maryam Rahmannia; Amir Hashem Shahidi Bonjar; Rosella Centis; Lia D'Ambrosio; Giovanni Sotgiu; Mohammad Javad Nasiri; Giovanni Battista Migliori (Karger Publishers, 2024)
Introduction: Osteoporosis poses a significant health concern, especially for individuals with chronic kidney disease (CKD). CKD disrupts mineral and bone metabolism, heightening the risk of fractures and complicating the management of osteoporosis. While anti-osteoporotic interventions aim to address bone health in CKD patients, ongoing research is essential to understand the comparative efficacy and safety of these medications, particularly in different CKD stages, notably in stages 4 and 5. Methods: We searched PubMed/MEDLINE, EMBASE, and the Cochrane CENTRAL for randomized controlled trials assessing the efficacy and safety of osteoporosis interventions in CKD up to June 15, 2024. The analysis utilized the pooled odds ratio (OR) along with the corresponding 95% confidence interval (CI), employing Comprehensive Meta-Analysis software, version 3.0. To assess heterogeneity in the results of individual studies, we used Cochran's Q statistic and the I2 statistic. Results: We analyzed 12 randomized controlled trials involving 31,027 participants, revealing a significantly lower risk of vertebral fractures with anti-osteoporotic agents (teriparatide, denosumab, romosozumab, raloxifene) compared to placebo (pooled OR, 0.28 [95% CI, 0.22-0.36]). Stratification by CKD stages showed a lower risk in Stages 1-3 but no significant reduction in stages 4 and 5. Teriparatide, denosumab, and romosozumab were effective in lowering fracture risk, whereas Raloxifene showed no significant effect. The lumbar spine, femoral neck, and total hip BMD showed no significant differences between anti-osteoporotic agents (denosumab, raloxifene, risedronate, alendronate, teriparatide) and placebo. However, romosozumab demonstrated a significantly greater BMD change in all kidney function categories. No reported side effects were observed in CKD stages 1-5 across the trials. Conclusions: Our meta-analysis highlights the effectiveness of anti-osteoporotic agents in lowering vertebral fracture risk in CKD patients, particularly in stages 1-3. However, this benefit is not apparent in stages 4 and 5, necessitating further research. Despite the absence of reported side effects in CKD patients, clinicians should carefully assess the suitability of these medications, considering individual risks and benefits.